Imunoestimulação pelo fungo Agaricus blazei: do alimento à inflamação - Juliana Lauar Gonçalves (2011)
Extracts of the mushroom Agaricus blazei (A. blazei), an edible mushroom, have been described as possessing immunostimulatory activities and is used as an alternative medicine for the treatment of many diseases. However, these effects of A. blazei as a functional food stuff have not been fully investigated in vivo. The aim of the present study was to investigate the effects of the A. blazei dietary treatment in experimental models of arthritis and atherosclerosis. Cellular phenotype analysis showed an increase in the splenic CD4+CD8+, CD49b+CD3+, CD11b+CD86+ populations and CD4+CD44high lymphocytes after six weeks of dietary treatment in apoE-/- mice. Extending the treatment to the twelfth week allowed detection of a systemic and splenic increase in CD49b+CD3- cells and Gr1+/Ly6G neutrophil population was also increased. Together, these cellular populations possibly contributes to atherogenesis, as treatment with A. blazei severely aggravated the injured area on the aortic valve and even increasing its instability by decreasing the intra-plaque collagen content. Pro-atherogenic genes, including the ones related to oxidized LDL uptake (SRA-2, CD36 and TLR4), the ones related to plaque vulnerability (MMP9 and CXCL-1) and to leukocyte adhesion (VCAM-1) were up regulated in the aortic arch by the treatment with A. blazei. However, in the arthritis model, treatment with A. blazei reduced dramatically neutrophil infiltration to the articular cavity as well as the number of leukocytes adhered to the knee microvasculature. Moreover, chemokines responsible for neutrophil (CXCL-1, CXCL-2) migration and also the cytokine IL-1β was significantly reduced, even though an increase in neutrophils CXCR-2high was detected. Although there was a decrease of the inflammatory activity in the antigen injection site, there was no change in parameters like hyper nociception or MPO activity in the periarticular tissue. Inversely to what is observed in non-challenged animals, treatment with A. blazei decreases the release of TNF-α in cultured splenocytes, what seems to indicate that the observed effects vary accordingly to the degree of cellular activation. Additionally, we detected an increase in cell death in the articular cavity, which points to a possible way through which A. blazei reduces the inflammatory response in this model. Taking all this into account, we can conclude that A. blazei causes a cellular immunostimulation, and, in the atherosclerosis model it assumes pro-atherogenic consequences but in the AIA model, it clearly displays an inhibitory effect in the local production of chemokines and in a decrease of the neutrophil infiltrate. Further studies are required to clarify the mechanisms through which A. blazei causes its effects in the arthritis model.